2005
DOI: 10.1007/s00467-005-1980-z
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic theophylline to prevent renal dysfunction in newborns exposed to perinatal asphyxia—a study in a developing country

Abstract: Renal damage frequently complicates perinatal asphyxia. Renal vasoconstriction due to adenosine metabolite leads to a fall in glomerular filtration rate (GFR) and filtration fraction. This might be inhibited by the nonspecific adenosine receptor antagonist, theophylline. This study was designed to determine whether theophylline could prevent and/or ameliorate renal dysfunction in term neonates with perinatal asphyxia. We randomized 40 severely asphyxiated term infants to receive intravenously a single dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
2
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 23 publications
3
57
2
3
Order By: Relevance
“…Several independent randomized studies in asphyxiated infants have shown that prophylactic theophylline, given early after birth, was associated with better kidney function. [70][71][72][73] As a result, the KDIGO guidelines recommend a single dose of theophylline for asphyxiated infants at risk for AKI. 44 Caution must be taken, as theophylline has some potentially harmful neurologic effects.…”
Section: Neonatal Cardiac Surgerymentioning
confidence: 99%
“…Several independent randomized studies in asphyxiated infants have shown that prophylactic theophylline, given early after birth, was associated with better kidney function. [70][71][72][73] As a result, the KDIGO guidelines recommend a single dose of theophylline for asphyxiated infants at risk for AKI. 44 Caution must be taken, as theophylline has some potentially harmful neurologic effects.…”
Section: Neonatal Cardiac Surgerymentioning
confidence: 99%
“…Furthermore, acute theophylline treatment given at 5 days after ischemia acutely increases renal blood flow and GFR in previously untreated rats, indicating that adenosine contributes to the suppression of renal blood flow and GFR in the maintenance phase of ischemic reperfusion injury (199). With regard to studies in humans, a single dose of theophylline, given early after birth, has beneficial effects in reducing the renal involvement and fall in GFR in asphyxiated full-term infants as determined over the first 5 days (14). In contrast, pretreating rats before renal artery occlusion for 30 min with dipyridamole, which increases extracellular adenosine concentrations, intensified the fall in renal blood flow and GFR determined ϳ1 h after releasing the clamp, and this impairment was blocked by theophylline (198).…”
Section: B Ischemia-reperfusion Injurymentioning
confidence: 99%
“…However, clinical trials are lacking in children for most of these medications. Several studies in neonates with perinatal asphyxia have suggested that a single dose of theophylline early after birth resulted in improved renal function and urine output [116][117][118]. Owing to the availability of standardized AKI definitions, the presence of renal tissue injury biomarkers, and the recent international recognition of AKI as an important condition to treat, several clinical trials (clinicaltrials.gov) are currently under way (some of these described in Table 7) and will hopefully lead to specific medical treatment or prevention of AKI in future years.…”
Section: Pharmacological Therapymentioning
confidence: 99%